Thomas Jefferson and Politics: “A game where principles are the stake” - Ari Helo (European Journal of American Studies)
Thomas Jefferson’s fame as an advocate of the eighteenth-century Enlightenment, equal rights of men, religious freedom, and democracy has been frequently questioned. For many scholars, his racist statements, his scant concern for women’s rights, his apparently unrealistic anti-slavery policies, and his anti-Federalist politics suffice as proof of the very opposite of his reputation. This article argues that politics can be viewed as the centerpiece of Jefferson's worldview, according to which all purposes needed to be brought into compliance, to the effect that one ended up with different politics for advocating democratic institutions, for progressive science, for personal self-development, and for socioeconomic issues, including slavery. The never-ending process of creating policies for bettering American society also gave politics its own character as a moral concept.